Long-term Consequences of Vietnam-Era Conscription: New Estimates Using Social Security Data - Angrist, Joshua D; Chen, Stacey H; Song, Jae (American Economic Review, 2011)
We use the draft lottery to construct instrumental variables (IV) estimates of the impact of Vietnam-era military service on veterans' Social Security (SSA) earnings through 2007. We also use SSA data to construct IV estimates for employment (as measured by an indicator for positive earnings) and disability status (as measured by an indicator for social security disability program application). New findings for recent years show surprisingly rapid convergence in veteran and nonveteran earnings: by the early 1990s, there was no longer a substantial Vietnam-era conscription penalty. The IV estimates also show no effect on employment or disability rates.